Diversi Sebagai Alternatif Penyelesaian pada Tindak Pidana yang Dilakukan oleh Anak : Studi Kasus pada Polres Madiun Kota - Revinta Irma Kartikasari; Subekti Subekti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Protection of children's rights in the Indonesian legal sistem has received serious attention with the enactment of Law Number 11 of 2012 concerning the Juvenile Criminal Justice Sistem (UU SPPA). This law emphasizes that imposing sanctions on children is not the primary goal, but rather a means to achieve child welfare through a restorative justice approach. The SPPA Law regulates two channels for resolving cases: formal justice and diversion. Diversion is a process for resolving children's cases outside the court system, aiming to prevent children from experiencing formal justice processes that have the potential to have long-term negative impacts on their psychological and social development. This study focuses on the implementation of diversion efforts during the investigation stage within the jurisdiction of the Madiun City Police. The method used in this study is an empirical method, namely by examining the implementation of the law in social realities in the field through observation and interviews with relevant parties. The results of the study indicate that the Madiun City Police have implemented diversion efforts quite well and in accordance with the provisions of the SPPA Law. The implementation of diversion is carried out by considering the principles of restorative justice and involving various parties, including child perpetrators, victims, families, and the police. However, several obstacles to implementing diversion exist, including a lack of public understanding of the concept and benefits of diversion, and frequent debates between perpetrators and victims, particularly regarding compensation issues within diversion forums. Therefore, increased public outreach and legal education, as well as stronger coordination between the institutions involved, are needed to optimally achieve the primary goals of the juvenile criminal justice system.